Electrochemistry and Spectroelectrochemistry of the Pu (III/IV) and (IV/VI) Couples in Nitric Acid Systems. Issue 12 (20th September 2017) - Lines, Amanda M.; Adami, Susan R.; Casella, Amanda J.; Sinkov, Sergey I.; Lumetta, Gregg J.; Bryan, Samuel A.
Abstract: The solution chemistry of Pu in nitric acid is explored via electrochemistry and spectroelectrochemistry. By utilizing and comparing these techniques, an improved understanding of Pu behavior and its dependence on nitric acid concentration can be achieved. Here the Pu (III/IV) couple is characterized using cyclic voltammetry, square wave voltammetry, and a spectroelectrochemical Nernst step. Results indicate the formal reduction potential of the couple shifts negative with increasing acid concentration and reversible electrochemistry is no longer attainable above 6 M HNO3 . Spectroelectrochemistry is also used to explore the irreversible oxidation of Pu(IV) to Pu(VI) and shine light on the mechanism and acid dependence of the redox reaction. Abstract :